2020
DOI: 10.1128/aac.00643-20
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Ravuconazole and Isavuconazole against Dematiaceous Fungi

Abstract: The in vitro activities of 11 antifungals against 84 dematiaceous fungi were tested. For most tested fungal species, the MIC values of ravuconazole and isavuconazole were lower than those obtained with itraconazole, voriconazole and posaconazole. Ravuconazole and isavuconazole appear to be more efficient against most dematiaceous fungal infection than other triazoles. However, some pigmented fungi such as B. spicifera and V. botryosa remain more susceptible to other triazoles or to echinocandins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Like other azoles, ravuconazole targets the CYP51 enzyme leading to the destabilization of the fungal cell wall. Although it shows good in vitro activity against several fungal species [19, [28][29][30][31][32][33][34], clinical studies on ravuconazole have been discontinued in 2007 due to bioavailability issues [35]. Fosravuconazole, a prodrug to ravuconazole has since been acquired by Eisai Ltd (Japan) and is currently being investigated in a randomised, double-blinded DNDi sponsored clinical trial for mycetoma [36].…”
Section: Discussionmentioning
confidence: 99%
“…Like other azoles, ravuconazole targets the CYP51 enzyme leading to the destabilization of the fungal cell wall. Although it shows good in vitro activity against several fungal species [19, [28][29][30][31][32][33][34], clinical studies on ravuconazole have been discontinued in 2007 due to bioavailability issues [35]. Fosravuconazole, a prodrug to ravuconazole has since been acquired by Eisai Ltd (Japan) and is currently being investigated in a randomised, double-blinded DNDi sponsored clinical trial for mycetoma [36].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of dematiaceous fungi makes susceptibility profiles valuable in determining the appropriate antifungal therapy for a given isolate. Given the lack of robust in‐vitro , pharmacokinetic, and pharmacodynamic data, as well as clinical outcomes data, there are no established MIC breakpoints for determining susceptibility; however, several genera have lower in‐vitro MICs for voriconazole, itraconazole, and posaconazole relative to fluconazole 193,194 . Ravuconazole and isavuconazole have also been found to have low MICs in certain species 194 .…”
Section: Discussionmentioning
confidence: 99%
“…193,194 Ravuconazole and isavuconazole have also been found to have low MICs in certain species. 194 We summarized reports that used BMD methods or of disseminated infections receiving combination therapy. 170 Disseminated infections in the present review received ≥ 2 antifungal agents more frequently (73%).…”
Section: F I G U R Ementioning
confidence: 99%
“… 14 Clinical case reports also showed that fungal melanonychia caused by different Candida spp. was successfully treated with oral fosravuconazole 15‐17 . It is, therefore, reasonable to expect that ravuconazole will become a new oral treatment option against other manifestations of candidiasis.…”
Section: Introductionmentioning
confidence: 99%
“…was successfully treated with oral fosravuconazole. [15][16][17] It is, therefore, reasonable to expect that ravuconazole will become a new oral treatment option against other manifestations of candidiasis.…”
mentioning
confidence: 99%